2000
DOI: 10.1348/000709900158083
|View full text |Cite
|
Sign up to set email alerts
|

The importance of music to adolescents

Abstract: These results indicate that music is important to adolescents, and that this is because it allows them to (a) portray an 'image' to the outside world and (b) satisfy their emotional needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
468
3
58

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(565 citation statements)
references
References 46 publications
36
468
3
58
Order By: Relevance
“…Similarly, other authors have pointed out the utilization of music activities and music listening for effective emotional regulation (self-regulation, DeNora, 1999;North et al, 2000), the establishment of self-identity , and the creation of interpersonal bonds (North & Hargreaves, 2007a, b, c). In a recent study, Chin and Rickard (2012) developed a self-report questionnaire (MUSE) and identified five sources of individual differences in musical engagement: engaged production, cognitive regulation, mood regulation, physical (dance and exercise), and social uses of music.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, other authors have pointed out the utilization of music activities and music listening for effective emotional regulation (self-regulation, DeNora, 1999;North et al, 2000), the establishment of self-identity , and the creation of interpersonal bonds (North & Hargreaves, 2007a, b, c). In a recent study, Chin and Rickard (2012) developed a self-report questionnaire (MUSE) and identified five sources of individual differences in musical engagement: engaged production, cognitive regulation, mood regulation, physical (dance and exercise), and social uses of music.…”
Section: Discussionmentioning
confidence: 87%
“…For example, in the sample by North and colleagues, healthy adolescents' reasons for listening differed quite widely, e.g. 'to relieve boredom', 'to help me through difficult times', 'to please friends', 'to reduce loneliness' (North, Hargreaves, & O'Neill, 2000). However, these authors did not examine associations between reasons for listening and indicators for physiological and psychological functioning in their participants.…”
Section: Introductionmentioning
confidence: 93%
“…In our experience, females generally exhibit music-induced shivers more frequently than males, and in accordance with the usage of most people, we will refer to this autonomic 'rush' as a 'chill' response. In this context, it is noteworthy that girls use music for mood regulation more than boys (North et al, 2000). In preliminary analysis of 'big five' personality dimensions (i.e.…”
Section: Music Body and Dancementioning
confidence: 99%